Converging migration routes of Eurasian hobbies Falco subbuteo crossing the African equatorial rain forest - Strandberg, Roine (The Royal Society, 2008)
Autumn migration of adult Eurasian hobbies Falco subbuteo from Europe to southern Africa was recorded by satellite telemetry and observed routes were compared with randomly simulated routes. Two non-random features of observed routes were revealed: (i) shifts to more westerly longitudes than straight paths to destinations and (ii) strong route convergence towards a restricted area close to the equator (1° S, 15° E). The birds migrated south or southwest to approximately 10° N, where they changed to south-easterly courses. The maximal spread between routes at 10° N (2134 km) rapidly decreased to a minimum (67 km) close to the equator. We found a striking relationship between the route convergence and the distribution of continuous rainforest, suggesting that hobbies minimize flight distance across the forest, concentrating in a corridor where habitat may be more suitable for travelling and foraging. With rainforest forming a possible ecological barrier, many migrants may cross the equator either at 15° E, similar to the hobbies, or at 30–40° E, east of the rainforest where large-scale migration is well documented. Much remains to be understood about the role of the rainforest for the evolution and future of the trans-equatorial Palaearctic-African bird migration systems.